2004
DOI: 10.1093/annonc/mdh222
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as a prognostic feature in operable breast cancer: the International Breast Cancer Study Group experience

Abstract: BMI is an independent prognostic factor for OS in patients with breast cancer, especially among pre-/perimenopausal patients treated with chemotherapy without endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 22 publications
13
165
4
4
Order By: Relevance
“…As indicated by our data, not taking HRT use into consideration could introduce spurious associations when analysing the influence of BMI on prognosis. However, two large and well-designed studies have found similar breast cancer survival regardless of BMI without taking HRT use into consideration (Dignam et al, 2003;Berclaz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by our data, not taking HRT use into consideration could introduce spurious associations when analysing the influence of BMI on prognosis. However, two large and well-designed studies have found similar breast cancer survival regardless of BMI without taking HRT use into consideration (Dignam et al, 2003;Berclaz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has repeatedly been associated with breast tumours of larger size, lymph node positivity, and poor prognosis Dal Maso et al, 2008), although some studies have produced contrasting findings (Dignam et al, 2003;Berclaz et al, 2004). However, many studies lack information on the use of hormone replacement therapy (HRT) and mammography examinations before diagnosis.…”
mentioning
confidence: 99%
“…Apart from the general increased breast cancer risk in obese women, obese breast cancer patients appear to have a worse prognosis relating to lymph node metastasis, tumor size, and death when compared with non-obese breast cancer patients [3,48,49]. Concerning A-FABP and tumor characteristics of breast cancer, to date, no data are available.…”
Section: Adipocytokines and Tnmmentioning
confidence: 99%
“…Several studies (Dignam et al, 2003;Berclaz et al, 2004;Loi et al, 2005) reported a higher risk of death in patients with BMI above 30 compared to those with a BMI less than 25. Furthermore, results from the Nurses' Health Study (Kroenke et al, 2005) showed that the association of weight gain after breast cancer diagnosis and increased breast cancer mortality was limited among women who had normal weight (BMI<25) before diagnosis.…”
Section: Introductionmentioning
confidence: 99%